Italy : Report on the Observance of Standards and Codes on FATF Recommendations for Anti-Money Laundering and Combating the Financing of Terrorism (AML/CFT). (IMF Staff Country Reports; Country Report, 2016)
This paper provides a summary of the anti-money laundering/combating the financing of terrorism (AML/CFT) measures in place in Italy and of the level of compliance with the Financial Action Task Force 40 (FATF 40) recommendations and the level of effectiveness, and contains recommendations on how the AML/CFT system could be strengthened. The assessment is based on the information available at the time of the mission from January 14-30, 2015, and other verifiable information subsequently provided by the authorities. It was conducted using the 2013 assessment methodology. The Detailed Assessment Report on which this document is based was adopted by the FATF Plenary on October 22, 2015.